Facile single-step ammonia heat-treatment and quenching process for the synthesis of improved Pt/N-graphene catalysts - Xiong, B.; Zhou, Y.; O'Hayre, R.; Shao, Zongping (Elsevier BV North-Holland, 2013)
In this work, we present a facile route to prepare electrocatalysts for methanol oxidation. The catalystsynthesis route involves the simultaneous reduction and nitrogen doping of graphene oxide (GO) along with the reduction of H2PtCl6 to Pt by a facile ammonia gas heat-treatment and quenching process. The resulting catalysts are characterized by X-ray diffraction, transmission electron microscopy, and X-ray photoelectron spectroscopy while their electrocatalytic activity toward the oxidation of methanol is evaluated by cyclic voltammetry. The obtained Pt/graphene composites consist of crystalline Pt nanoparticles in the range of 1–4 nm which are well-dispersed on the N-doped graphene sheets. The best Pt/N-graphene catalyst composite is obtained after a 5 min ammonia treatment at 800 ?C followed by rapid ammonia gas quenching at room temperature. This catalyst demonstrates superior catalytic activity for methanol electro-oxidation, with a peak current density of 0.218 A mgPt-1, which is about five times higher than an undoped (hydrogen treated and quenched) Pt/graphene control catalyst. The excellent electrocatalytic performance of the ammonia quenched catalyst is attributed to the nitrogenous functional groups and dopants in the graphene sheets that are formed during the facile quenching process in ammonia.